A Discrete Model for HIV Infection with Distributed Delay - Brahim EL Boukari; Khalid Hattaf; Noura Yousfi (International Journal of Differential Equations)
We give a consistent discretization of a continuous model of HIV infection, with distributed time delays to express the lag between the times when the virus enters a cell and when the cell becomes infected. The global stability of the steady states of the model is determined and numerical simulations are presented to illustrate our theoretical results.